Influences on cognitive outcomes in adult patients with gliomas: A systematic review - Kirkman, Matthew A.; Hunn, Benjamin H. M.; Thomas, Michael S. C.; Tolmie, Andrew K. (Frontiers in Oncology, 2022)
People with brain tumours, including those previously treated, are commonly affected by a range of neurocognitive impairments involving executive function, memory, attention, and social/emotional functioning. Several factors are postulated to underlie this relationship, but evidence relating to many of these factors is conflicting and does not fully explain the variation in cognitive outcomes seen in the literature and in clinical practice. To address this, we performed a systematic literature review to identify and describe the range of factors that can influence cognitive outcomes in adult patients with gliomas. A literature search was performed of Ovid MEDLINE, PsychINFO, and PsycTESTS from commencement until September 2021. Of 9,998 articles identified through the search strategy, and an additional 39 articles identified through other sources, 142 were included in our review. The results confirmed that multiple factors influence cognitive outcomes in patients with gliomas. The effects of tumour characteristics (including location) and treatments administered are some of the most studied variables but the evidence for these is conflicting, which may be the result of methodological and study population differences. Tumour location and laterality overall appear to influence cognitive outcomes, and detection of such an effect is contingent upon administration of appropriate cognitive tests. Surgery appears to have an overall initial deleterious effect on cognition with a recovery in most cases over several months. A large body of evidence supports the adverse effects of radiotherapy on cognition, but the role of chemotherapy is less clear. To contrast, baseline cognitive status appears to be a consistent factor that influences cognitive outcomes, with worse baseline cognition at diagnosis/pre-treatment correlated with worse long-term outcomes. Similarly, much evidence indicates that anti-epileptic drugs have a negative effect on cognition and genetics also appear to have a role. Evidence regarding the effect of age on cognitive outcomes in glioma patients is conflicting, and there is insufficient evidence for gender and fatigue. Cognitive reserve, brain reserve, socioeconomic status, and several other variables discussed in this review, and their influence on cognition and recovery, have not been well-studied in the context of gliomas and are areas for focus in future research.